Does carbon emission trading policy affect bank loans of firms? Evidence from China. Issue 18 (24th October 2022) - Yu, Zhi; Cao, Yali; Liu, Mo
ABSTRACT: Using a carbon emission trading pilot policy in China, we construct a DID method to investigate the effect of carbon emission trading on corporate financial behaviour. We find that enterprises in the pilot areas get less bank loans after the 'pilot policy', which indicates that carbon emissions trading has a negative impact on debt financing. Additional analysis shows that the negative influence is more significant in state-owned enterprises. Our study provides a more complete picture of the microeconomic impact of carbon emissions trading, and improves our understanding of the role and significance of corporate 'carbon assets' in the capital market.